Induced Pluripotent Stem Cell-Based Systems for Personalising Epilepsy Treatment: Research Ethics Challenges and New Insights for the Ethics of Personalised Medicine. Issue 2 (3rd April 2022) - Walker, Mary Jean; Nielsen, Jane; Goddard, Eliza; Harris, Alex; Hutchison, Katrina
ABSTRACT : This paper examines potential ethical and legal issues arising during the research, development and clinical use of a proposed strategy in personalized medicine (PM): using human induced pluripotent stem cell (iPSC)-derived tissue cultures as predictive models of individual patients to inform treatment decisions. We focus on epilepsy treatment as a likely early application of this strategy, for which early-stage stage research is underway. In relation to the research process, we examine issues associated with biological samples; data; health; vulnerable populations; neural organoids; and what level of accuracy justifies using the iPSC-derived neural tissue system. In relation to clinical use, we examine potential uses in pre-natal screening, and effects on clinical decision-making. Although our focus is providing recommendations for researchers developing work in this area, we identify the novel issue of deciding on an acceptable accuracy level for the system. We also emphasize an issue thus far neglected in the ethics of PM: PM tends to represent treatment decisions as though they should be directed solely by biomedical information, but this in itself could be detrimental to best personalizing treatment decisions in the clinic.